The seen and be heard study: A national mixed methods study to identify the barriers and facilitators to ensuring equitable cancer care for children with and without learning disabilities and/or who are autistic – Protocol Paper - Kate Oulton; Jo Wray; Mary Foo-Caballero; Samantha Flynn; Phillip Harniess; Anupama Rao; Faith Gibson (PLoS ONE, 2025)
Introduction A strong body of evidence exists relating to inequality in general healthcare experience and outcomes for children and young people with learning disabilities and/or who are autistic compared to those without. Healthcare practitioners describe feeling less capable and confident to deliver care to children with learning disabilities, as well as having less capacity. However, there is little research specifically in cancer care that explores access and acceptability of provision for children with learning disabilities and/or those who are autistic. This is despite some cancers being more prevalent in syndromes associated with learning disabilities, for example Down’s Syndrome. We aim to explore the needs and experiences of children with/without learning disabilities and/or who are autistic and their families receiving cancer care. This inclusive study will provide evidence of whether, and what, inequity exists, for whom and why, generating evidence of what issues affect all children and young people receiving cancer care and what are particular to those with learning disabilities and/or who are autistic. Methods and analysis We will use a transformative mixed methods design, comprising an individual staff and organisational level survey, retrospective case note review, ethnographic observations of clinical care, family and staff interviews, and participatory workshops. The ethnographer will follow and observe individual children and their families. We will use a ‘toolbox’ of creative participatory methods, including providing a co-designed research data collection journal to support elicitation of the child’s perspective. Data will be analysed using thematic analysis. The study will run from January 2025 to January 2026. The project is registered on ClinicalTrials.gov (Identifier: NCT06481527). Health Research Authority approval has been granted (REC Reference no. 24/LO/0410 | IRAS Project ID: 335623). Discussion The mixed methods approach using survey and qualitative design will support a broad scope and in-depth understanding of the barriers and facilitators to inform equitable cancer care delivery for children with and without learning disabilities and/or who are autistic. Potential limitations are acknowledged. For example, resource constraints mean that the focus of the ethnography work package is within two hospital sites, which may limit broader comparisons and thematic development. Dissemination of findings will include papers specific to each work package. Recommendations for clinical practice will be developed, including staff training, healthcare planning and innovative solutions for improving the cancer care experience. These outputs will directly inform quality improvement from a local to national and international context in cancer care around children and young people with learning disabilities and/or who are autistic.